Green Synthesis of Silver Nanoparticles using Curcuma xanthorrhiza as an Antibacterial Agent Against Staphylococcus aureus - Adieba Warda Hayya; Ainun Nadjib (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2026)
This study synthesized silver nanoparticles (Cur-AgNPs) using Curcuma xanthorrhiza rhizome extract via a green synthesis method to address the growing concern of nosocomial infections. Nosocomial infections, particularly those caused by Staphylococcus aureus, remain a significant healthcare challenge due to increasing antimicrobial resistance. The aim of this study was to evaluate the antibacterial activity of Cur-AgNPs against Staphylococcus aureus. Silver nanoparticles were synthesized using 1 mM AgNO₃ at 60°C for 24 h, followed by characterization using UV-Vis spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy (SEM). Antibacterial activity was assessed using the disk diffusion method at concentrations of 10, 20, 40, 80, and 160 μg/mL, with Clindamycin as a positive control. The results showed that Cur-AgNPs exhibited concentration-dependent antibacterial activity, with inhibition zones ranging from 5 ± 0.25 mm to 15 ± 0.89 mm, while the positive control (Clindamycin) produced an inhibition zone of 14 ± 0.2 mm. These findings suggest that Cur-AgNPs possess promising in vitro antibacterial activity against Staphylococcus aureus. However, this study is limited to a single bacterial species and in vitro evaluation. Further studies are required, including minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assays, cytotoxicity testing, nanoparticle stability analysis, and evaluation in in vivo models to confirm their potential biomedical applications.